Pengaruh Kualitas Laba terhadap Nilai Perusahaan - Siallagan, Hamonangan (Widya Mandala Surabaya Catholic University, 2009)
The purpose of this research is to investigate and give empirical evidence o f the effect of earnings quality on firm value. The proposed hypotheses is earnings quality positively influence value of the firm. To test alternative hypotheses, this research used manufacturing listed on Jakarta Exchange Stock which issue financial statement. Purposive sampling is used f or data collection with 74 manufacturing sample and Observation sum 197.The result indicates that earnings quality influence the value of The Firm. The earnings quality of proxy stated by Sloan (1996), chan et al. (2001) and Warfielde t al. (1995)i s discretionary accruals.